Análisis de vulnerabilidad de las redes inalámbricas del departamento de operaciones y mantenimiento en la empresa CNT Babahoyo - Mantuano Zúñiga, Byron Alejandro (2019)
Wireless networks are a type of connection that allows access to the multiple advantages offered by the global network, for this it is essential to have an appropriate speed that allows maintaining an adequate connection and thus perform network activities in an optimal way. This type of connection also has several disadvantages, all linked to safety and speed. The use of network analysis tools allows to know the level of vulnerability of these connections, allowing precautionary measures to be taken to correct and prevent the loss of information. In companies it is essential to have secure wireless networks that allow them to carry out internal activities in an appropriate way, meeting the proposed objectives and meeting the needs of those who use the services. To correct those security problems in wireless networks and their services there are several tools that help in this activity